Toward qualification of additively manufactured metal parts: Tensile and fatigue properties of selective laser melted Inconel 718 evaluated using miniature specimens. (20th January 2022) - Wan, H.Y.; Yang, W.K.; Wang, L.Y.; Zhou, Z.J.; Li, C.P.; Chen, G.F.; Lei, L.M.; Zhang, G.P.
Highlights: A "microstructure unit" that can well reflect the microstructure characteristic of SLM materials is defined. As the ratio of specimen thickness( t ) to the "microstructure unit" size( d ) is reduced below one, a dramatic decrease in tensile ductility occurs. A criterion of t/d ≥ 4 for reliable mechanical properties determined by the miniature specimens is obtained. Abstract: Combined with the topology optimization, additive manufacturing can be used to fabricate metal parts with complex shapes. However, due to the geometrical variations and microstructure heterogeneities of the additively manufactured metal parts, new standards with the use of miniature specimens are required for the evalutation of the spatial distribution of mechanical properties throughout the parts. Here, we conduct a systematic investigation on tensile and fatigue properties of selective laser melted Inconel 718 specimens with different thicknesses ranging from 0.1 mm to 1 mm. A "microstructure unit" that can well reflect the microstructure characteristic of selective laser melted materials is defined. The results reveal that premature necking with a dramatic drop in uniform elongation occurs if the ratio ( t/d ) of specimen thickness ( t ) to the "microstructure unit" size ( d ) is less than one. Premature necking is mainly attributed to the transition of strain localization behavior. We also propose a probabilistic statistical model for fatigue limit prediction based on the available fatigue data. It is recommended that the criterion of t/d ≥ 4 should be satisfied to ensure that the yield strength, the uniform elongation, and the fatigue limit determined by the miniature specimens are comparable with those determined by standard specimens. The findings may provdie a guide to the establishment of miniature specimen-based standards toward the qualification of additively manufactured metal parts. Graphical abstract: Image, graphical abstract